SERUPA TAPI TAK PERNAH SAMA: GENEOLOGI IDENTITAS HIBRID ARTIS BLESTERAN INDO-EROPA DI INDUSTRI PENYIARAN (SEBUAH TINJAUAN POSKOLONIAL) - Lasido, Nur Allan (Fakultas Dakwah dan Komunikasi, 2022)
This article explains how the origin (genealogy) of the hybrid identity of Indo-European artists has a special place on the stage of the Indonesian broadcasting industry beyond the existing Indonesian artists and actually has traces of the history of the Dutch colonial occupation era. The purpose of the article to analyze the traces of Dutch colonial memory is related to the strengthening of the existence of Indo-European Artists. Through the theory of postcolonial theory, the author uses it to examine colonialism discourses that can still be traced in the broadcasting industry in Indonesia post-New Order period. This article explains that the interest of some people in the appearance of Indo artists, can be traced in trace from the history of colonialism occupation in the Dutch East Indies, that the existence of Indo-European people is a bad history of mountainous practices in former colonies. So the status as